Proactive Technological Policy and Import Substitution Perspectives: The Role of Testing Centers - I. V. Anokhov (Ekonomika Nauki)
The purpose of the article is the investigation of proving grounds and testing centers role in proactive technological development of the country. The object of the study is the Experimental Loop of Railway Research Institute, which have a unique, almost century-long history of testing activities. The article investigates features of reactive and proactive science and technology policy. It is proven that currently science and technology policy should have strongly marked nature. Existing methods and ways of evaluation, including Technology Readiness Level (TRL) scale may be implemented. The main development stages of the Experimental Loop internal structure and functions are analysed. The perspective ways of its development are proposed, which imply the transition from reactive to proactive technological policy in order to develop a certain branch.